Single-port laparoscopic ovariectomy using a pre-tied loop ligature in Santa Ines ewes - Barros,Felipe Farias Pereira da Câmara (2015)
ABSTRACT: The aim of the study was to develop and assess the feasibility, postoperative pain and inflammatory response of the single-port laparoscopic ovariectomy in ewes, using a simple pre-tied loop ligature technique. Pre-tied Meltzer's knot was employed for prophylactic hemostasis of the ovarian pedicle. Slipknot was inserted within the abdominal cavity through a 14-gauge needle and tied surrounding the ovarian pedicle. Mean surgical time, manipulation, ligature and resection of each ovary and anesthesia time were 63±20, 20±10 and 91±26 minutes, respectively. No bleeding occurred during the surgeries. Ewes showed low scores pain (0.5±0.5) at all time-points. Postsurgical plasma fibrinogen was within the normal range for sheep specie at all time-points. The ewes showed a significant weight gain in comparison to the basal scaling (one day before the surgery). Single-port laparoscopic ovariectomy using a pre-tied loop ligature is feasible in the ovine specie and provided minimal postoperative distress and quick weight gain.